2016
DOI: 10.5755/j01.ee.27.4.14713
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Corporate Social Responsibility and its Implementation in Practice: The Case of Lithuanian Small and Medium-Sized Enterprises

Abstract: Recent reports in media and research findings in the scientific literature suggest the growing importance of corporate social responsibility among practitioners, especially in the case of small and medium-sized enterprises that are characterised by limited resources required to adequately compete in the fast changing macro-environment. Previous research still lacks clarity about perceived corporate social responsibility, its strengths and challenges that small and medium-sized enterprises face when implementin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…CSR and CG are discussed in a substantial number of studies in management literature (Salciuviene et al, 2016). These concepts offer an understanding of the role of business in society and economy developing at the macro, meso, and micro levels.…”
Section: Origin and Evolution Of Csr And Cgmentioning
confidence: 99%
See 1 more Smart Citation
“…CSR and CG are discussed in a substantial number of studies in management literature (Salciuviene et al, 2016). These concepts offer an understanding of the role of business in society and economy developing at the macro, meso, and micro levels.…”
Section: Origin and Evolution Of Csr And Cgmentioning
confidence: 99%
“…However, both concepts have been developing separately (Bhimani & Soonawalla, 2005), proposing competitive views on how business should be done and what goals should be achieved. The review of the existing literature indicates that both concepts are still far from providing answers to these questions; however, after years of conflicting approaches, it is possible to identify mutual links and synergies and offer a broader, more holistic view on companies (Beltratti, 2005;Jamali et al, 2008;Kolk & Pinkse, 2010;Salciuviene et al, 2016). The research problem in this article refers to the identification of the relationship and synergies between CSR and CG at the company level.…”
Section: Introductionmentioning
confidence: 99%
“…Lithuanian organizations have recorded stable progress in implementing CSR, when limited progress was achieved in improving the structural preconditions for CSR in society. Regardless of the progress achieved, empirical studies indicate several open issues regarding CSR's implementation in organizations and society (Salciuviene, Hopeniene, & Dovaliene, 2016). For example, Vasiljeviene and Vasiljev (2005) revealed that organizations in Lithuania favor profits over CSR and find economic CR more important than natural and social CSR.…”
Section: Corporate Social Responsibility In Lithuania and Sloveniamentioning
confidence: 99%
“…From 15 selected SMEs a total of six SMEs' managers/owners agreed to participate. Small sample sizes are usual in studies developing a theoretical model for further research (Salciuviene, Hopeniene, & Dovaliene, 2016). Furthermore, according to Morse (1994) in the case of the phenomenological study, at least six participants are recommended.…”
Section: Case Selectionmentioning
confidence: 99%